KONTRIBUSI MINAT BACA DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 2 BUKITTINGGI - Mustyka, Olyvia (JURNAL PENDIDIKAN ROKANIA, 2017)
This study aimed to describe the following. First, the contribution to the writing skills reading a text description of the class VII SMP Negeri 2 Bukittinggi. Second, the contribution of motivation to learn to write text descriptions skills class VII SMP Islam Khaira Ummah. Third, the contribution of interest in reading and learning motivation together to write a text description of the skills the students of class VII SMP Negeri 2 Bukittinggi. The population of this study were all students of class VII SMP Negeri 2 Bukittinggi which consists of three classes with the number of students 85 people. Sampling was done by total sampling that took the entire population to be made in the sample because the population is less than 100 persons who are 85 students. This research instrument in the form of a questionnaire that has been tested for validity and reliability and performance test writing skills text descriptions. This research data in the form of a score reading, learning motivation and writing skills scores were converted to a text description in the form of value. Data were analyzed using Pearson Product Moment correlation test (PPM), multiple correlation test, t test, F test, and determinant coefficient formula to determine the contribution of the independent variable on the dependent variable, both individually and collectively-sama.Berdasarkan research can be concluded that the following three things. First, interest in reading and relationships contribute significantly to the learning outcomes Indonesian; Second, learning motivation and relationships contribute significantly to the learning outcomes Indonesian. Third, interest in reading and learning motivation jointly contribute and significant relationship to the text description of students' writing skills